Hudde en Spinoza: waarom er maar één God is - van Bunge, Wiep (Studium, 2018)
In 1666 Johannes Hudde had a brief but important epistolary exchange with the philosopher Spinoza. Hudde had probably been triggered by Spinoza’s demonstration of God’s uniqueness, delivered in his introduction to Cartesianism of 1663. Hudde turned out to be a tenacious correspondent, not easily satisfied and he inspired Spinoza to elucidate his own metaphysics which at the time had not been pub- lished yet. Meanwhile, Spinoza had to be careful: he was fully aware of the heterodox nature of his own metaphysics, according to which for instance extension is one of God’s attributes. Hudde on the other hand deserves credit for identifying a major puzzle in Spinoza’s metaphysics, for if God’s attributes are indeed as autonomous as Spinoza wants them to be, how are they able to constitute a single God?